2014
DOI: 10.1097/yco.0000000000000106
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sleep on the risk of cognitive decline and dementia

Abstract: Purpose of review Trouble falling or staying asleep, poor sleep quality, and short or long sleep duration are gaining attention as potential risk factors for cognitive decline and dementia, including Alzheimer's disease (AD). Sleep-disordered breathing (SDB) has also been linked to these outcomes. Here, we review recent observational and experimental studies investigating the effect of poor sleep on cognitive outcomes and AD and discuss possible mechanisms. Recent findings Observational studies with self-rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
165
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 250 publications
(173 citation statements)
references
References 48 publications
3
165
2
3
Order By: Relevance
“…44 Further, OSA may be a risk factor for progression of mild cognitive impairment to dementia and poor sleep been implicated in the pathogenesis of Alzheimer disease. 45 These findings raise the possibility that WMH may modulate some of the neurological complications of OSA.…”
Section: Discussionmentioning
confidence: 96%
“…44 Further, OSA may be a risk factor for progression of mild cognitive impairment to dementia and poor sleep been implicated in the pathogenesis of Alzheimer disease. 45 These findings raise the possibility that WMH may modulate some of the neurological complications of OSA.…”
Section: Discussionmentioning
confidence: 96%
“…Previous narrative review articles that have examined this association did so with a focus on different aspects of sleep disturbances/disorders. [16][17][18][19] Palma et al, 16 focusing on sleep deprivation, reviewed how sleep loss constitutes a risk factor for various neurologic diseases including AD. Slats et al, 18 focusing on the role of hypocretin and melatonin, concluded that there is substantial evidence for impairments in both sleep and circadian regulating mechanisms resulting from AD pathology, which may be linked to clinical symptoms.…”
Section: Study Results In Comparison To Other Reviews On the Topicmentioning
confidence: 99%
“…If this is true, they could be critical to the goal of preventing this disease because effective interventions exist to improve sleep. 15 Narrative review articles examining this association [16][17][18][19] reflect the opinion and consensus among specialists that there is growing experimental and epidemiologic evidence for a close reciprocal association of cognitive impairment and AD with sleep problems and disorders. However, to date, no review has quantified the effect of having sleep problems and disorders on cognitive impairment and AD.…”
Section: Introductionmentioning
confidence: 99%
“…A growing literature suggests that reduced sleep quality and duration may be risk factors for subsequent cognitive decline and dementia. 81,82 Moreover, sleep disruption has been found to contribute to the onset and accumulation of Alzheimer pathology. 83 Given the elevated risk of dementia associated with PTSD 84,85 as well as with TBI, [86][87][88] consideration of sleep as a mediating factor of long-term cognitive outcomes will be of critical importance.…”
Section: Discussionmentioning
confidence: 99%